Critical Review of Nursing Involvement in X-Ray Imaging: Enhancing Procedures and Patient Experience - Alyami, Awatef Khuder Mesfer; Al dawi, Safia Thaban Hamad; Alsaleem, Doaa Mouse Saleh; Alnasib, Nadia Mohammed Saad; Alyami, Huda Sultan Saad; Al Saeed, Fatima Hassan Saeed; Alyami, Wedad Ali Marzooq; Al Obyah, Batool Mohamad Salim; Al Yami, Maha Saad Jumaan; Naggar, Aziza Mohammed Ahmed (Journal of Ecohumanism, 2024)
This paper aims to critically discuss the growing responsibilities of nursing professionals relative to radiography and X-ray imaging techniques. Traditionally, nursing staff were more or less passive participants in radiological procedures, if they participated at all—they often simply prepared the patient and occasionally assisted the radiographer if needed. Nurses have become less involved in radiologic settings, but as the functional capacities of nurses continue to be extended, their participation in radiologic settings is increasing. This review aims to evaluate the effect of the implemented nursing mediations in terms of the technical efficiency in the X-ray imaging process, safety, and patient satisfaction. Also, the paper examines the training and education required for nurses to assume these roles successfully, as well as the advantages and limitations of enhancing the involvement of nurses in diagnostic imaging. Applying the results of the literature review and case studies, the review underlines the lack of interdisciplinary cooperation. It states several recommendations for improving patient care in a radiological setting.